Learning of Islamic Education Through Padlet and Quizizz Material the History of Islamic Civilization of the Prophetic Period: Mekkah, and Madinah Periods - Khairuni, Nisa (Jurnal Riset dan Pengabdian Masyarakat, 2025)
Students can benefit greatly from studying the history of Islamic civilization, but regrettably, this cannot be reflected in learning objectives. When studying history, notably the history of Islamic culture, one constantly gets the feeling that it is monotonous and boring. This article therefore addresses the use of Quizizz and Padlet to teach the history of the prophetic period: the Mecca and Medina periods. By using this platform, PAI learning, the material will be more engaging and inspire students to learn more about the prophetic period. This paper's methodology is gathering information from a variety of literature that is pertinent to the issues raised and doing a descriptive analysis of it. Thus, in order to overcome